Evaluation of phytochemical, trace metals content, antioxidant and antimicrobial potential of Bonnaya Ruellioides (Colsm.) Spreng: An ethnomedicinal plant of North Eastern India - Singh Maharabam, Kishorjit; Ronibala , kram; S. Laitonjam, Warjeet; Khunjamayum, Rakhi; Singh Chingakham, Brajakishor; Birla Singh, Kshetrimayum (Edelweiss Applied Science and Technology, 2024)
Bonnaya ruellioides (Colsm.) Spreng is an ethnomedicinal plant widely found in Manipur, a northeastern state of India and it belongs to the Linderniaceae family. The study aimed to evaluate the phytochemical content, trace metals, antioxidant and antimicrobial activity of this ethnomedicinal plant in various extracts including chloroform, petroleum ether, ethyl acetate, methanol, and water extracts. Phytochemical analysis was done using standard protocols, trace metals content by using Atomic Absorption Spectrophotometer (AAS), antioxidant by DPPH, Reducing Power and ABTS assay. Antimicrobial activity of the plant was also determined by Zone of Inhibition (ZOI) assay. Phytochemicals such as phenol, saponin, flavonoid, alkaloid, and terpenoid were detected in the water extract, whereas tannin, glycoside, flavonoid, steroid, alkaloid, and terpenoid were found in the plant extracts of petroleum ether, chloroform, and ethyl acetate. Trace elements detection using AAS revealed the presence of Fe (0.298 ± 0.011 mg/g), Zn (0.083 ± 0.003 mg/g), Cu (0.024 ± 0.002 mg/g) and Mn (0.014 ± 0.002 mg/g) in the plant. Further, evaluation of antioxidant activity using DPPH scavenging assay in chloroform and methanol extracts recorded 411.59 ±2.62 IC50 (μg/mL ± SD) and 80.96 ± 0.68 IC50 (μg/mL ± SD) respectively. Reducing power activity of the chloroform and methanol extracts showed 249.27 ± 1.48 μM FeSO4/mg sample and 44.55 ± 0.47 μM FeSO4/mg sample, respectively, and for ABTS assay, 281.82 ± 2.19 TEAC/g dw and 168.65 ± 2.06 TEAC/g dw are recorded respectively. The antimicrobial study of the chloroform and petroleum ether extracts showed negative results for all the selected pathogens of bacterial and fungal strains. At the same time, the methanol extract showed positive for bacterial strains including Micrococcus luteus (17.50 ±0.54) mm and Escherichia coli (15.0 ± 2.0) mm, while negative for all the fungal strains. The results of the study demonstrated for the ﬁrst time that B. ruellioides plant has notable phytochemical, essential trace metals, promising antioxidant and antimicrobial capacity. Thus, the findings of our study will contribute a scientific insight into the therapeutic applications of this ethnomedicinal plant in folklore medicines and enable the prediction of further applications in drug development.